Cellulose nanofiber aerogels impregnated with bio-based epoxy using vacuum infusion: Structure, orientation and mechanical properties. (8th February 2018) - Nissilä, Tuukka; Karhula, Sakari S.; Saarakkala, Simo; Oksman, Kristiina
Abstract: Cellulose nanofiber aerogels were used as preforms that were impregnated with a bio-epoxy resin via a widely used vacuum infusion process. The simple and straightforward nanocomposite processing approach resulted in an almost 70% improvement in the storage modulus of the polymer with only an 11.7 wt% cellulose nanofiber content. The nanofibers were well dispersed in the polymer matrix and the fiber structures were anisotropically aligned. The impregnation time of the aerogels was also significantly lower than that of the more commonly used nanopapers. It was thus shown that environmentally friendly and mechanically robust nanocomposites could be produced by impregnating cellulose nanofiber aerogels with a thermosetting resin using a processing approach that has potential to be scaled up for commercial use.